2022
DOI: 10.1590/1980-220x-reeusp-2021-0548en
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological distress and fear of Covid-19 in student nurses before clinical placement: a cross-sectional study

Abstract: Objective: To determine the degree of psychological distress and fear of COVID-19 experienced by undergraduate student nurses who were about to begin their clinical placements. Method: A cross-sectional study was carried out with 100 second- and third-year undergraduate student nurses of the University of Zaragoza (Spain). Measures included the Fear of COVID-19 Scale and the Depression Anxiety Stress Scales. Results: Regularly, student nurses did not think of themselves as vulnerable to COVID-19. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…This study indicated that most nursing students were very stressed, and stress levels were negatively associated with satisfaction in online learning. Students’ stress levels, measured 18 months after the pandemic started, were higher than stress levels measured with the same tool in prior studies conducted in the initial months of the COVID-19 pandemic [ 27 , 28 ]. Nursing students consistently report higher stress levels than other college students [ 29 ], however, the higher stress levels in the present study may reflect the cumulative and prolonged effects of the transition to online learning, meeting academic expectations, limited socialization, and fear of contagion.…”
Section: Discussionmentioning
confidence: 60%
“…This study indicated that most nursing students were very stressed, and stress levels were negatively associated with satisfaction in online learning. Students’ stress levels, measured 18 months after the pandemic started, were higher than stress levels measured with the same tool in prior studies conducted in the initial months of the COVID-19 pandemic [ 27 , 28 ]. Nursing students consistently report higher stress levels than other college students [ 29 ], however, the higher stress levels in the present study may reflect the cumulative and prolonged effects of the transition to online learning, meeting academic expectations, limited socialization, and fear of contagion.…”
Section: Discussionmentioning
confidence: 60%
“…Además de las condiciones laborales precarias, la literatura reporta la escasez o inexistencia de equipo de protección y la falta de recursos para la atención del COVID-19. En Brasil, Subirón-Valera (2022) señala que la conducta de los estudiantes de enfermería que entran a prácticas clínicas generalmente es de confianza y seguridad pero que durante el COVID-19 se observaron mayores niveles de distrés psicológico y miedo 27 . Ramaccioti (2022) reporta para Argentina también la contratación temporal, la falta de equipo de protección y la escasez de recursos 28 .…”
Section: Discussionunclassified
“…Besides precarious working conditions, the literature reports the scarcity or non-existence of protective equipment and the lack of resources for COVID-19 care. In Brazil, Subirón-Valera (2022) pointed out that the behavior of nursing students entering clinical practices is generally one of trust and safety, but that higher psychological distress and fear levels were observed 27 during COVID-19. Ramaccioti (2022) also reported temporary hiring, the lack of protective equipment, and scarcity of resources 28 in Argentina.…”
Section: Discussionmentioning
confidence: 99%